Quantum and pattern of intimate partner violence: An epidemiological study in a tertiary care hospital of Srinagar, Uttarakhand - Dixit, Sumeet; Singh, Amit Kumar; Bandhani, Aradhana (Indian Journal of Community Health, 2014)
Background: Intimate partner violence (IPV) has been increasingly recognized as a public health problem associated with serious medical, family, and societal effects. Violence against women is a major public health problem and violations of women's human rights, with substantial repercussions for women’s physical, mental, sexual, and reproductive health. This necessitates information on quantum and pattern of IPV, for effective interventions. Methods: This cross-sectional, randomized hospital based survey of married women aged 15–49 years took place in a tertiary care hospital in Srinagar, Uttarakhand from November 2012 to March 2013, using the methodology of WHO Study on Women’s Health and Domestic Violence. Data analysis has been done using SPSS version 15.0 and Microsoft office excel 2007. To test significance, chi square test have been used as applicable. Results: Prevalence of current IPV was 31.83% in the present study. IPV was found significantly associated with socio-economic status of the family, education of the female, drinking behavior of the husband and economic dependence of female on husband. Religion, age of the female and duration of marriage were non-significant predictors for intimate partner violence in the present study. Conclusions: The study documented prevalence, patterns and determinants of intimate partner violence. Efforts, targeting the most vulnerable, and measures like IPV awareness, Female education, vocational training program for females, legal literacy should be promoted. These measures can prove valuable for effective control of IPV and related mortality/morbidity/other significant repercussions on female well-being.